Routes, places et stratégies du « business » transnational entre Casablanca (Maroc), Nouakchott (Mauritanie) et Dakar (Sénégal) - Anne Bouhali; Nora Mareï (L'Espace Politique)
This article analyses the dynamics of economic, social, and political linkages on a West African axis between Morocco, Mauritania, and Senegal, focusing on the commercial sphere and its modalities (commercial spaces, transportation of goods, actors). This article analyses the dynamics of economic, social, and political linkages on a West African axis between Morocco, Mauritania, and Senegal, focusing on the commercial sphere and its modalities (commercial spaces, transportation of goods, actors). Combining analyses of the strategies of institutional actors (in particular the role of the Moroccan state) and those of transnational trade actors (migrants, entrepreneurs, transnational firms), we examine the type of macro-region that is under construction between these countries, which are strongly bound by human and trade flows. To understand the dynamics of regionalisation underway, a multi-sited and pluri-annual qualitative approach has been favoured. The different places we studied - markets, border crossings, streets or neighbourhoods known for their boutiques selling imported products, parking lots serving as both resting places and trading areas - are all specific entry points and anchors for understanding regional geopolitics and the strategies at work among economic and political actors along the trans-Saharan route that connects Tangier to Dakar.